2002
DOI: 10.1590/s1517-74912002000200012
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de periodontite agressiva em adolescentes e adultos jovens do Vale do Paraíba

Abstract: The aim of the present study was to determine the prevalence of localized and generalized aggressive periodontitis, as well as of incidental attachment loss, in a population of adolescents and young adults aging between 15 and 25 years (19.4 +/- 3.44) from Vale do Paraíba - SP, who searched for general dental care at the Department of Dentistry, University of Taubaté, São Paulo. Six hundred patients, 244 male and 356 female subjects, were included in the studied sample. The periodontal status of this populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
1
10
0
2
Order By: Relevance
“…The continents covered were Africa (Albandar, Muranga, & Rams, ; Elamin, Skaug, Ali, Bakken, & Albandar, ; Harley & Floyd, ; Haubek et al, ; Kissa et al, ), with 2 Moroccan studies (Haubek et al, ; Kissa et al, ), Asia (Ababneh, Hwaij, & Khader, ; Albandar, ; Cho, You, & Jeong, ; Ereş, Sarıbay, & Akkaya, ; Kowashi, ; Levin, Baev, Lev, Stabholz, & Ashkenazi, ; Nanaiah, Nagarathna, & Manjunath, ; Roozegar, Havasian, Panahi, & Hashemian, ; Sadeghi, ; Uchiyama et al, ; Yee, Subramaniam, Raman, & Loo, ), Europe (Hoover, Ellegaard, & Attström, ; Kronauer, Borsa, & Lang, ; Petruţiu et al, ; Saxby, ; Saxén, ) and north America (Barnett, Baker, & Yancey, ; Horning, Hatch, & Lutskus, ; Löe & Brown, ; Melvin, Sandifer, & Gray, ; Neely, ) and south America (Corraini, Pannuti, Pustiglioni, Romito, & Pustiglioni, ; Cortelli, Cortelli, Pallos, & Jorge, ; Hermes, Baumhardt, & Rösing, ; López, Ortueta, & Hdez, ; López, Ríos, Pareja, & Fernández, ; Susin & Albandar, ; Tinoco et al, ). The years of publication ranged from 1980 to 2016.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The continents covered were Africa (Albandar, Muranga, & Rams, ; Elamin, Skaug, Ali, Bakken, & Albandar, ; Harley & Floyd, ; Haubek et al, ; Kissa et al, ), with 2 Moroccan studies (Haubek et al, ; Kissa et al, ), Asia (Ababneh, Hwaij, & Khader, ; Albandar, ; Cho, You, & Jeong, ; Ereş, Sarıbay, & Akkaya, ; Kowashi, ; Levin, Baev, Lev, Stabholz, & Ashkenazi, ; Nanaiah, Nagarathna, & Manjunath, ; Roozegar, Havasian, Panahi, & Hashemian, ; Sadeghi, ; Uchiyama et al, ; Yee, Subramaniam, Raman, & Loo, ), Europe (Hoover, Ellegaard, & Attström, ; Kronauer, Borsa, & Lang, ; Petruţiu et al, ; Saxby, ; Saxén, ) and north America (Barnett, Baker, & Yancey, ; Horning, Hatch, & Lutskus, ; Löe & Brown, ; Melvin, Sandifer, & Gray, ; Neely, ) and south America (Corraini, Pannuti, Pustiglioni, Romito, & Pustiglioni, ; Cortelli, Cortelli, Pallos, & Jorge, ; Hermes, Baumhardt, & Rösing, ; López, Ortueta, & Hdez, ; López, Ríos, Pareja, & Fernández, ; Susin & Albandar, ; Tinoco et al, ). The years of publication ranged from 1980 to 2016.…”
Section: Resultsmentioning
confidence: 99%
“…We included 24 population‐based studies (Albandar, ; Albandar et al, ; Corraini et al, ; Elamin et al, ; Ereş et al, ; Harley & Floyd, ; Haubek et al, ; Hoover et al, ; Kissa et al, ; Kowashi, ; Kronauer et al, ; Löe & Brown, ; López et al, , ; Nanaiah et al, ; Neely, ; Petruţiu et al, ; Roozegar et al, ; Sadeghi, ; Saxby, ; Saxén, ; Susin & Albandar, ; Tinoco et al, ; Uchiyama et al, ) and 9 hospital‐based studies (Ababneh et al, ; Barnett et al, ; Cho et al, ; Cortelli et al, ; Hermes et al, ; Horning et al, ; Levin et al, ; Melvin et al, ; Yee et al, ).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…These estimates are confirmed by studies conducted with the Brazilian population [4][5] . A study performed in São Paulo showed that 45% of the subjects presented some degree of periodontal impairment and 5% presented severe PD 6 . The association between PD and cardiovascular atherosclerotic disease has received a great deal of attention [7][8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%